SISTEM PENUNJANG KEPUTUSAN PEMILIHAN CALON KETUA RT MENGGUNAKAN METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) - Bagas Adi Putra; Ahmad Fauzi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Attribute decision-making method that can be used to support decision makers in selecting several alternatives. In its process, the SMART method uses a linear adaptive model for the value of each alternative. In the selection process for the acceptance of the RT Head candidate, there are many assessments including income, age, education, and residence ownership. In this study, the selection process will be carried out using the Simple Multi-Attribute Rating Technique (SMART) method. This method selects alternative criteria that have predetermined values and weights, to obtain qualified and appropriate candidates for RT heads. Based on the results of system testing, it was concluded that the Simple Multi Attribute Rating Technique Method was effective enough to be applied in determining the acceptance of qualified candidates for RT heads at Puri Pamulang Housing, RT03/RW09, South Tangerang.